Таксономічний та типологічний аналіз флори лучних пасовищ на південному сході України - Шевчук, О.М. (Промышленная ботаника, 2003)
An analysis of the taxonomy and typology of the meadow pastures flora of the Ukraine’s south-east was performed. At present, the flora comprises 475 species of 206 genera and 48 families, that makes up 24% of species, 34% of genera and 37% of the total number of the families of the regional flora. A significant number of species of the dry habitats (27%), those with a short life cycle (31%), adventive (13%) and the species of synanthropophyton (16%) was revealed, that testifies to a considerable anthropogenous transformation of the meadow phytocenoses.